Hemopericardium with subsequent cardiac tamponade secondary to rivaroxaban treatment: a case report. Issue 1 (11th December 2020) - Shastri, Pinang; Bhuta, Sapan; Oostra, Carson; Monroe, Todd
Abstract: Background: The use and utility of novel oral anticoagulants has been increasing in clinical practice due to their relatively lower incidence of side effects such as intracranial haemorrhage, particularly in the elderly, when compared with vitamin K antagonists. Rivaroxaban is a factor Xa and prothrombinase inhibitor indicated for stroke and venous thromboembolism prophylaxis in non-valvular atrial fibrillation as well as treatment of venous thromboembolism. Case summary: A patient with history of paroxysmal atrial fibrillation on Rivaroxaban presented with generalized malaise, lightheadedness, and dizziness. The patient was found to be in profound cardiogenic shock despite unremarkable cardiac enzymes. Electrocardiogram revealed rate controlled atrial fibrillation and T-wave inversions in the inferolateral leads without associated electrical alternans. Bedside echocardiogram revealed a large pericardial effusion consistent with cardiac tamponade physiology. Following anticoagulation reversal, the patient underwent urgent pericardiocentesis yielding haemorrhagic fluid, with subsequent improvement in haemodynamic status. Despite the presence of retroperitoneal lymphadenopathy on previous computed tomography of the abdomen and concern for underlying malignant effusion secondary to lymphoma, cytology of the fluid revealed no evidence of malignant cells and follow-up flow cytometry and bone marrow biopsy were unremarkable. Discussion: While hemopericardium is not listed as a known side effect of Rivaroxaban, previous cases of hemopericardium secondary to Rivaroxaban have been described in the literature secondary to pre-disposing risk factors including CYP450 drug interactions or cardiac device implantations. In this case, the patient experienced a spontaneous hemopericardium on Rivaroxaban without any previously elucidated risk factors or evidence of malignancy.